Global Monitoring Report 2015/2016 : Development Goals in an Era of Demographic Change - World Bank; International Monetary Fund (Washington, DC: World Bank, 2015)
The Global Monitoring Report 2015/2016, produced by the World Bank Group in partnership with the International Monetary Fund, comes at an inflection point in both the setting of global development goals and the demographic trends affecting those goals.